Enzymatic synthesis of structured lipids with behenic acid at the sn-1, 3 positions of triacylglycerols - Kok, Wai Ming; Chuah, Cheng Hock; Cheng, Sit Foon (Springer, 2017)
A long chain saturated fatty acid (SFA), behenic acid, is incorporated into the sn-1, 3 positions of triacylglycerols in palm olein (POo) and high-oleic sunflower oil (HOS) by solvent-free interesterification catalyzed by Lipozyme RM IM. The enzymatic interesterified HOS (EIE-HOS) yielded 76.5% of BOO and BOB as compared to 45.6% in POo (EIE-POo). The sn-2 position of EIE-HOS displayed 5.3 mol% of SFA which is significantly lower compared to 13.5 mol% in EIE-POo (P < 0.001). The sn-1, 3 positions of EIE-POo exhibited greater amount of behenic acid (82.0 mol%) in relation to EIE-HOS (64.0 mol%) (P < 0.001). Due to the greater variety of constitutive triacylglycerol, EIE-POo showed greater differences between onset (To) and offset temperature (Tf) in the melting endotherms (76.99 °C) as compared to EIE-HOS (68.65 °C), and may offer more intensive cooling sensation and flavor release.